Citra Diri Profesi Arsitek di Media Sosial TikTok: Studi Kasus terhadap Personal Branding Ariq Naufal pada Akun @Riqmann - Pegary Paras putri; Retno Dyah Kusumastuti (Brand Communication, 2022)
Ariq Naufal is an architect who works as a content creator on TikTok. Through his content, Ariq Naufal provides information and education about architecture close to ordinary people's lives. Therefore, this study seeks to explain more about the self-image of an architect on social media through the formation of personal branding that he does. The research method used in this study is a qualitative method that seeks to explore and explain the meaning that comes from a social problem and uses a case study approach in which it seeks to develop and evaluate an in-depth analysis of a problem. Data collection techniques used in this study were observation and interviews. The researcher used four stages of data analysis belonging to Miles & Huberman, whose contents were data collection, data reduction, data presentation, and concluding/verification. To analyze the personal branding built by Ariq on TikTok social media, the researcher uses Peter Montonya's eight personal branding concepts and a dramaturgical approach. The study found that Ariq had implemented the eight personal branding concepts on his TikTok account. Besides that, Ariq has also built a positive self-image as an architect who shares information about architecture on TikTok